Інклюзивність розвитку аграрного сектору і сільських територій: сучасний стан та інструменти забезпечення - Степаненко, С. В. (My University, 2022)
У статті розглянуто склад базових домінантів та сутнісних характеристик інклюзивного розвитку. Систематизовано сукупність проблемних факторів, які супроводжують процес соціально-економічного розвитку аграрного сектору і сільських територій України на сучасному етапі. Проведено аналіз ключових індикаторів соціально-економічної інклюзії агросектору і сільських територій. Визначено, що фактичний стан розвитку агросфери і сільських територій України супроводжується значними диспропорціями та наявністю дисбалансу між потребами і можливостями населення села. Величезними розривом характеризуються також індикатори інклюзії у контексті порівняння рівня якості життя сільського і міського населення країни. Вирівнювання існуючих диспропорцій можливо забезпечити за рахунок розробки і імплементації інклюзивної моделі розвитку агробізнесу і сільських територій, для якої було обґрунтовано сукупність інструментів внутрішньої та зовнішньої інклюзії. Становлення і функціонування інклюзивної моделі розвитку агробізнесу в Україні сьогодні має бути синхронізовано із ключовими принципами соціальної відповідальності аграрного бізнесу та сталого розвитку, які визначені пріоритетними як у національних, так й у європейських стратегічних планах. The composition of the basic dominants and essential characteristics of inclusive development is considered in the article. The set of basic components of the architecture of inclusive development under modern realities is complemented by the principles of sustainable development, the principles of a high level of innovative activity and digitalization of socio-economic relations. The results of the research helped to systematize a set of problematic factors that accompany the process of socio-economic development of the agrarian sector and rural areas of Ukraine today. An analysis of key indicators of socio-economic inclusion of the agricultural sector and rural areas has been carried out. The results showed that the most complex trends are uneven formation and distribution of income in agriculture, different employment opportunities for residents of rural areas and access to conditions of decent wages, structural imbalance and the growth of the share of informal rural employment, uneven distribution of the net financial result within the corporate agricultural sector and households. creation of an inclusive agribusiness model, strategically oriented to ensure and increase the level of inclusive business activity in the context of the global initiative for the sustainable development of agribusiness and rural areas, is one of the real directions for solving these problems. Institutional support is necessary to ensure the implementation and operation of an inclusive model of agribusiness. The tools of the inclusive model are proposed to be divided into internal and external. The internal tools included: socially oriented marketing, inclusive business operations, inclusive innovations, finance and investment, inclusive micro-business environment. The composition of internal tools consists of: schools of business leaders in the field, specialized coordination structures, financial instruments of state and partner support for agro-inclusion, information technology support in the format of creating modern online digital platforms. The effective interaction of these components should form the prerequisites for increasing the level of inclusiveness in the development of agribusiness and rural areas and the basis for the transition to a strategy of sustainable development.
Inclusiveness of the development of the agrarian sector and rural areas: current status and provision instruments
Keywords: інклюзивний розвиток; аграрний бізнес; сільські території; сталий розвиток; модель агробізнесу; населення; якість життя; inclusive development; agrarian business; rural areas; sustainable development; agribusiness model; population; quality of life